LOYALITAS KONSUMEN DITINJAU DARI PERSEPSI TERHADAP CITRA PERUSAHAAN - Sayekti, Retno Putri; Hardjanta, George; Savitri, Anna Dian (Faculty of Psychology, Diponegoro University, 2012)
This research aims to empirically examine the relationship between perception of corporate image and consumer loyalty. The hypothesis accompanying this research was a positive relationship between perception of corporate image and customer loyalty. Samples in this research were 77 consumers of Central Laundry Semarang. This research used incidental sampling technique and two scales, i.e. consumer loyalty scale and perception of corporate image scale. Data analysis was performed using product moment correlation technique. Results showed that there was a significant positive relationship between perceptions of corporate image to the consumer loyalty as indicated by the value of rxy = 0.371 (p <0.01). Therefore the hypothesis of this study was accepted.Keywords: consumer loyalty, perception, corporate image